DevOps: proposição de um guia de implementação - Fernandes, Tereza Cristina Maia (2019)
The new technological conjuncture, with multiple and different approaches, has been making changes in the way organizations use the information technology, with the objective of improving performance and achieving higher rates of competitiveness. On the other hand, business areas require that their products and services are delivered with higher speed, quality and at lower cost, demanding that the development of systems becomes more agile and lean. One of the answers to the necessities for faster and continuously implementations was the use of agile methods, with a significant reduction on the software development deadlines. However, the installation and operation of the systems did not advance at the same speed. For a vigourous action in the resolution of this miss match between development and infrastructure, the IT community initiated the DevOps movement which its main focus is the communication and collaboration between development and operations teams, resulting in a faster and more effective workflow. DevOps in its essence is a cultural movement. This research aims to address the challenges and experiences in the implantation of the DevOps’ pillars and practices, in addition of proposing a guide focused on software development companies, so that they can use it as a guidance for the implementation of this new culture. The study uses qualitative and exploratory approach, using interviews with support of Delphi method that applied along with the DevOps experts and IT managers allow you to evaluate whether the enablers related to the pillars and practices of the DevOps culture are enough to direct a proposal of a guide for your implementation.